Prospects of animal models and their application in studies on adaptive immunity to SARS-CoV-2 - Wei, Xiaohui; Rong, Na; Liu, Jiangning (Frontiers in Immunology, 2022)
The adaptive immune response induced by SARS-CoV-2 plays a key role in the antiviral process and can protect the body from the threat of infection for a certain period of time. However, owing to the limitations of clinical studies, the antiviral mechanisms, protective thresholds, and persistence of the immune memory of adaptive immune responses remain unclear. This review summarizes existing research models for SARS-CoV-2 and elaborates on the advantages of animal models in simulating the clinical symptoms of COVID-19 in humans. In addition, we systematically summarize the research progress on the SARS-CoV-2 adaptive immune response and the remaining key issues, as well as the application and prospects of animal models in this field. This paper provides direction for in-depth analysis of the anti-SARS-CoV-2 mechanism of the adaptive immune response and lays the foundation for the development and application of vaccines and drugs.